Cosmopolitanism in children: a cause (sociological) just - Natália Fernandes Soares; Catarina Tomás (Universidade Federal de Santa Catarina, 2009)
The century begins now appears to be paradoxical, it is a world of wonders and great achievements, but also of barbarism, extreme economic ambition and strong inequalities.